2000
DOI: 10.1097/00005344-200009000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol Induces NO-Mediated Relaxations of Rat Small Mesenteric But Not of Large Elastic Arteries

Abstract: Nebivolol is a newer beta1-selective adrenergic receptor antagonist, which unlike classic beta-blockers, lowers systemic vascular resistance by direct vasodilator effects possibly involving NO. This study was designed to determine the effects of nebivolol on small arteries, which contribute to the most part of systemic vascular resistance. Mesenteric arteries, isolated from 9-week-old Wistar-Kyoto (WKY) rats, were studied under perfused and pressurized conditions using a video dimension analyzer. Aortic rings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…The pharmacological effects of nebivolol have been studied in vitro on segments of mouse thoracic aorta [8,9] , canine coronary and carotid artery [10] , rats and bovine aorta and small mesenteric arteries [3,11,12] , on human aortic smooth muscle cells (SMC) [13] , as well as on the coronary endothelial and smooth muscle cells [14,15] . These studies showed that nebivolol has a vasodilatory effect [8][9][10][11][12] , reduces the cell proliferation [13][14][15] , does not significantly influence glucose or plasma lipid metabolism, and appears to have a protective effect on the left ventricular function [6] . However, the mechanisms through which nebivolol induces all these effects are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological effects of nebivolol have been studied in vitro on segments of mouse thoracic aorta [8,9] , canine coronary and carotid artery [10] , rats and bovine aorta and small mesenteric arteries [3,11,12] , on human aortic smooth muscle cells (SMC) [13] , as well as on the coronary endothelial and smooth muscle cells [14,15] . These studies showed that nebivolol has a vasodilatory effect [8][9][10][11][12] , reduces the cell proliferation [13][14][15] , does not significantly influence glucose or plasma lipid metabolism, and appears to have a protective effect on the left ventricular function [6] . However, the mechanisms through which nebivolol induces all these effects are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental evidence indicates that the drug's vasodilating effects depend on endothelium-dependent mechanisms 3 as inferred from their attenuation by nitric oxide synthase (NOS) and soluble guanylyl cyclase inhibitors [3][4][5][6] in different vascular beds and species, including humans. [7][8][9] However, the nature of the transduction pathway as well as the identity of the potential receptor that mediates nebivolol's activation of endothelial nitric oxide synthase (eNOS) leading to vasodilation remain elusive.…”
mentioning
confidence: 99%
“…The blood pressuredecreasing effect of nebivolol and carvedilol seems to result from a direct vasorelaxant effect of the drugs not mediated by adrenoceptors but possibly by NO generation from endothelial cells. This suggestion comes from studies that relied on the determination of the secondary effects of NO, eg, vasorelaxation after inhibition of NO synthesis or endothelium removal 2,4,6,7 or the measurements of biologically inactive products of NO, eg, nitrites, 5,8 but not based on direct measurement of NO. Therefore, it is still unclear whether ␤-blockers themselves augment NO production, and the presence of an endogenous mediator of the vasodilating effect of the drugs is suspected.…”
mentioning
confidence: 99%
“…It has been shown that nebivolol and carvedilol specifically caused relaxation in rat small arteries, 2,6,7 which may be effective in protecting the microcirculation in various cardiovascular disease states. Vascular tone in arterial microvasculature is controlled by both perivascular nerves and endothelial cells.…”
mentioning
confidence: 99%